The critical role and potential target of the autotaxin/lysophosphatidate axis in pancreatic cancer - Ming Quan; Jiu-jie Cui; Xiao Feng; Qian Huang (Tumor Biology)
Autotaxin, an ecto-lysophospholipase D encoded by the human ENNP2 gene, is expressed in multiple tissues, and participates in numerous critical physiologic and pathologic processes including inflammation, pain, obesity, embryo development, and cancer via the generation of the bioactive lipid lysophosphatidate. Overwhelming evidences indicate that the autotaxin/lysophosphatidate signaling axis serves key roles in the numerous processes central to tumorigenesis and progression, including proliferation, survival, migration, invasion, metastasis, cancer stem cell, tumor microenvironment, and treatment resistance by interacting with a series of at least six G-protein-coupled receptors (LPAR1–6). This review provides an overview of the autotaxin/lysophosphatidate axis and collates current knowledge regarding its specific role in pancreatic cancer. With a deeper understanding of the critical role of the autotaxin/lysophosphatidate axis in pancreatic cancer, targeting autotaxin or lysophosphatidate receptor may be a potential and promising strategy for cancer therapy.